A mixed computational modelling and experimental approach to the interaction between gold nanoparticles and blood proteins - Giza, Marta Serra (2016)
Upon arrival at the bloodstream, injected gold nanoparticles are covered with circulating plasma proteins, creating what is called a plasma corona. Its protein content is determined by the proteins’ affinity constants to the exposed surface of the nanoparticle. This work aims to propose an interaction mechanism between three plasma proteins and CALNN-functionalized nanoparticles via computational simulation and complementary experimental approach. Denaturing polyacrylamide gel electrophoresis determined the protein content of two human plasma samples, and helped in the characterization of the three most abundant blood proteins used in this study. Estimation of their electrostatic potential surfaces, silhouette areas, and diameters allowed the evaluation of the theoretical number of proteins forming a fully-covered nanoparticle. Seventeen transferrin molecules and eighteen albumin molecules with a side-on adsorption orientation were predicted to represent a monolayer adsorbome in a 20 nm gold nanoparticle. The dynamics of albumin adsorption to nanoparticles was studied through incubation-time assays on agarose gel electrophoresis, resulting in a stable protein corona starting from 7 h incubation time. The concentration ratio forming protein corona at the surface of nanoparticles was analysed through agarose gels electrophoretic mobility assays, revealing the formation of a full protein corona when a plateau in bionanoconjugates migration is achieved, resulting in protein coronas of [HSA]:[AuNP-CALNN] of 200:1 and 600:1 for [BPF]:[AuNP-CALNN] concentration ratios. Zeta-potential values were derived by relating agarose percentage with electrophoretic mobility of albumin bionanoconjugates, resulting in lower potential values for bionanoconjugates due to surface charge shielding of nanoparticles. Obtained ζ-potential values ranged from -26.05 up to -20.36 mV, forming colloid stable bionanoconjugates. Hydrodynamic radii of bionanoconjugates of albumin supported the formation of a monolayered and two-layered protein corona with increasing albumin:nanoparticle concentration ratios. Transferrin and fibrinogen showed increasing hydrodynamic radii with increasing protein:nanoparticle concentration ratios; in which fibrinogen bionanoconjugates showed fibrinogen wrapping around the nanoparticle. Electrostatic potential surfaces and protein-ligand docking using nanoparticle’s capping agent CALNN was performed in order to predict possible adsorption sites of human albumin and transferrin.